Nursing diagnoses and outcomes related to the circulatory-system terms (ICNP®) represented in an ontology - Marcia Regina Cubas; Arianny Macedo Brondani; Andreia Malucelli (SciELO, 2013)
The aim of the present study was to develop titles of Nursing Diagnoses and Outcomes (ND/NO) through the relationship between the terms of the Focus axis, limited to the Circulatory System Process, and the terms of other ICNP® axes and to integrate these terms into an ontology. Titles were developed linking 17 terms of the focus axis, which were evaluated by expert nurses in five Brazilian cities. Titles whose use concordance was above 0.80 were included in the ontology. In total, 89 titles for ND/NO were supported in the literature, and 19 were not supported; 37 were assessed as eligible for use in healthcare practice and were included in the ontology. The construction of ND/NO titles based on the ICNP® and using a formal representation of knowledge is a task that requires deepening concepts used for nursing and adequate classification revisions. The elaborated titles will facilitate the composition of diagnostics that are more consistent with practice.